Penelitian Pengembangan Media Pembelajaran Interaktif Diorama Metamorfosis Terhadap Hasil Belajar IPAS - Khalimatus Sya’diah; Mukhammad Hendry Ansyah; Naila Adinda Habibah; Nafisa Putri Aji; Siti Masfuah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The aim of this research is to find out the results of the development of interactive media diorama metamorfosis against the learning results of IPAS. This research uses quantitative methods with the research method is quantitatively descriptive. The data gathering techniques used in this study include observations, interviews, and lifting. Subjects in this study are 2 teachers and 5 students of SD 2 Jurang. The analysis technique is quantitative descriptive analysis with the help of Ms. Excle data processing software. The research data obtained was carried out V Aiken test. Based on the above data, it can be known that the results of the validation test of teaching materials and media Diorama Metamorfosis carried out by the teacher as a validator obtained an average score of ≤ 0,82, which means that the data received can be said to be very valid, effective, and worthy to be a support for learning. Meanwhile, the results of the validation test conducted by 5 students obtained the same score that is about ≤ 0.88 so that it can be concluded that the results show very valid and effective data, so that can be used in the student learning process.